2021
DOI: 10.1038/s42005-021-00663-8
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced enhancement of superconductivity in iron-based superconductor FeSe0.5Te0.5

Abstract: Illumination of light on matter normally causes heating and destroys the ordered ground states. Despite this common understanding, recent advances in ultrafast light sources have enabled the non-thermal control of quantum phases. Here, we report the light-induced enhancement of superconductivity in a thin film of an iron chalcogenide FeSe0.5Te0.5, which exhibits multiple quantum condensates associated with the multi-orbital character. Upon the photoexcitation, we observed a transient increase of the superfluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 73 publications
(90 reference statements)
0
17
0
Order By: Relevance
“…In the former case, the authors observed marked oscillations of the transmitted signal as a function of the pump-probe delay t pp at a frequency corresponding to twice the smaller gap. This result [34,35] implies a marked resonance of the non-linear kernel at the lowest optical gap, as also suggested by THG experiments in FeSe 0.5 Te 0.5 [38]. However, to really establish the predominance of the Higgs over the BCS response one would need again to estimate the role of disorder for each band, that was not explicitly provided in Ref.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the former case, the authors observed marked oscillations of the transmitted signal as a function of the pump-probe delay t pp at a frequency corresponding to twice the smaller gap. This result [34,35] implies a marked resonance of the non-linear kernel at the lowest optical gap, as also suggested by THG experiments in FeSe 0.5 Te 0.5 [38]. However, to really establish the predominance of the Higgs over the BCS response one would need again to estimate the role of disorder for each band, that was not explicitly provided in Ref.…”
Section: Discussionmentioning
confidence: 84%
“…In the present manuscript we provide a detailed analysis of the non-linear response of multiband superconductors, with the twofold aim from one side to clarify the nature of the collective fluctuations, in particular the Higgs mode, and from the other side to establish the experimental conditions for their detection via non-linear optics, that has been recently applied both to MgB 2 [24,27] and iron-based superconductors [37][38][39]. For what concerns the amplitude fluctuations, we will show that the redistribution of spectral weight between the two peaks at 2∆ α in the spectral functions depends crucially on the structure of the coupling matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, coherent modes (phonon, collective excitations, etc) can be also triggered in [7][8][9][10][11][12][13][14][15][16]. A later probe (optical, electronic, transport, diffraction) is thus used to assess the physical properties at a time delay t. Within this context, pump-probe experiments have proven to be able to induce a variety of physical processes otherwise not allowed (or very slow) under steady conditions, as for instance insulator-metal transitions [17][18][19][20][21][22][23], light-induced superconductivity [24][25][26][27][28][29], chemical reactions [30][31][32][33][34], structural phase transitions [17,35], local heat-transport, non-linear optics [14,36,37], exciton dynamics of relevance for light harvesting [38][39][40], detecting the effects of surface plasmons and/or other collective modes [41,42], manipulation of magnetic degrees of freedom [43][44][45][46] etc. In accordance with the different physical processes under examination, a wide variety of time-resolved techniques have been developed, encompassing an...…”
Section: Introductionmentioning
confidence: 99%
“…1) The excitation and relaxation of quasiparticles and collective modes have been observed by pump-probe spectroscopy. 2,3) As a major development, the amplitude mode, which was difficult to observe because it did not appear in the linear response, has been discussed in the nonlinear response with experimental [4][5][6][7] and theoretical methods. [8][9][10][11][12] On the other hand, the generation of nonequilibrium states is possible not only by optical excitation but also by stationary fields (magnetic field and current), which has been studied for a long time.…”
Section: Introductionmentioning
confidence: 99%